Corporate Investment in Human Capital Accumulation as a Condition for Social Well-Being; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Nedospasova O. P. Olga Pavlovna (2017, 2017)
Title screen